Interleukin‐31 and itch in dermatomyositis. (17th September 2018) - Kim, H.J.; Zeidi, M.; Bonciani, D.; Pena, S.M.; Tiao, J.; Sahu, S.; Werth, V.P.
Summary: Patients with dermatomyositis often suffer from itching, but the mechanism is unknown. The authors of this study, based in USA, Korea and Italy, aimed to find out how common itch is in patients with dermatomyositis, and whether a cytokine called IL‐31 is increased in affected skin. Cytokines are proteins produced by cells in the immune system and a delicate balance of cytokines is needed to maintain health. In some skin disorders, such as atopic eczema, this balance is disrupted, and too many pro‐inflammatory cytokines (meaning ones which cause inflammation) are produced. 191 patients with the condition were surveyed, and the authors took biopsy samples from skin lesions, compared with four healthy controls (people without dermatomyositis). They found that half of the patients had moderate to severe itch, and itch was linked to the severity of the disease. In skin lesions from patients with itchy dermatomyositis, there was increased gene expression of IL‐31and its receptor (meaning more IL‐31 and the receptor that helps it work were released), and this expression was stronger in patients with more severe itch. A new drug under investigation for dermatomyositis, lenabasum, reduces or 'downregulates' the expression of IL‐31, and the authors conclude that it may prove to be of value in the treatment of itch in this condition. Abstract : Linked Article:  Kim et al. Br J Dermatol 2018;179 :669–678